The Impact Of Dividend Policy, Managerial Ownership, Institutional Ownership To Capital Structure On Manufacturing Company In Indonesia Stock Exchange (Idx) Period 2012-2016 - Ratna Putri Indah Puspita; Suherman Suherman (Journal of Business and Behavioural Entrepreneurship, 2018)
This study aims to determine the effect of dividend policy, managerial ownership and institutional ownership on the capital structure of manufacturing companies listed on the IDX for the 2012-2016 period. The data used in this study is an annual report of the Manufacturing Sector listed on the IDX for the period 2012-2016. By using purposive sampling method, 56 companies were obtained and consisted of 280 observations. The model used in this research is panel data analysis using the Random Effect Model approach. The results of this study indicate that the dividend policy has a positive but not significant effect on DER, but has a significant positive effect on DAR. While managerial ownership is influential but not significantly negative on the capital structure (DER and DAR). Institutional ownership has a significant negative effect on DER, but has a negative but not significant effect on DAR. Profitability has a significant negative effect on the capital structure (DER and DAR), while the structure of assets and company size does not have a significant effect on the capital structure. (DER and DAR).